Minat Melakukan Pencatatan Akuntansi Melalui Pendidikan, Umur Usaha, Dan Komitmen Organisasi Pada Industri Kecil Menengah Kabupaten Jepara - yanto yanto; Shalihul Aziz Widya Iriawan; Fatchur Rohman (Jurnal Akuntansi dan Perpajakan, 2019)
Abstract The purpose of this study is to analyze the interests of accounting records through education, age of business, and commitment. The sample of research is 89 IKM in Jepara regency, sampling technique using random sampling. Analyzer uses multiple regression, hypothesis test, and coefficient of determination. The results of the analysis is known to have a significant influence on the importance of accounting records, evidenced by testing the hypothesis t is the value of sig. 0.001. Age of business does not have a significant influence between the interest to perform accounting records, evidenced by testing the hypothesis t is the value of sig. 0.740. And organizational commitment has a significant influence on interest in accounting records, evidenced by testing the hypothesis t is the value of sig. 0,000. Keywords: Education, Age, Commitment, and Accounting Recording. DOI: https://doi.org/10.26905/ap.v5i1.2568 //